Growth And Development of Kovrak (Ferula L) In Surkhandarya Region - Begmatov Abdusamat Mamatkulovich; Rakhmatova Masuma Umarovna (Zien Journals, 2021)
This article analyzes the research and literature of many botanicals, floristic and systematic scientists on the bioecological features, systematics, geographical distribution, growth and development of Ferula L
Keywords: Ferula L; asafetida; essential oils; resin